The Relationship among Motivation, Attitudes, and Learning Achievement of English as a Foreign Language at Del Institute of Technology - Santi Agustina Manalu (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
English is a mandatory course learned by the students of Del Institute of Technology. One of graduates’ quality targets is the ability of English language indicated by TOEFL score at least 515. Motivation and attitudes are considered important determinants in learning language. This study investigated the relationship among students’ learning motivation, attitudes and their English learning achievement at Del Institute of Technology. The attitudes analyzed were students’ attitude towards English learning, English language, English towards native speaker, and English lecturer. The research design used was the analysis of quantitative correlation. The data were taken by distributing a questionnaire to 120 respondents and interviewing them randomly. The result showed that students’ learning motivation in English was medium indicated by (M=2.90) on a scale from 1 – 4, attitude towards learning English was positive (M=2.90), attitude towards English language (M=3.39), attitude towards English native speaker was positive (M=3.01), attitude towards English lecturer was positive (M=3.14). The findings also showed that there is no significant relationship among motivation, attitudes and learning achievement. It is predicted that the other factors might be the determinant in increasing English learning outcome that will lead to the investigation for further research.